Larvicidal activity of Zinc oxide and titanium dioxide nanoparticles Synthesis using Cuscuta reflexa extract against malaria vector (Anopheles stephensi). Issue 1 (1st January 2020) - Soni, Namita; Dhiman, Ramesh C.
ABSTRACT: In this present study, the Zinc oxide nanoparticles (ZnO NPs) and Titanium dioxide nanoparticles (TiO2 NPs) were synthesized using the aqueous stem extract of the Indian parasitic plant Cuscuta reflexa . Further, the synthesized nanoparticles were tested as larvicidal activity against the malaria vector, Anopheles stephensi larvae. The synthesized nanoparticles were characterized with UV-visible spectroscopy, X-rays powder diffraction (XRD), Transmission electron microscopy (TEM), scanning electron microscopy with Energy-dispersive X-ray spectroscopy (SEM-EDS). The mortality of larva was observed after 48 h by probit analysis. The synthesized ZnO NPs and TiO2 NPs were spherical in shape, and 40.86 nm and 85.58 nm in size, respectively. The TiO2 NPs were found highly effective against the larvae of An. stephensi (100% mortality in the first and fourth instar, 50–90% mortality in second instar, and 40–80% mortality in third instar larvae) than the ZnO NPs and aqueous stem extract. The present study reveals the first report of the synthesis of ZnO NPs and TiO2 NPs using the aqueous stem extract of C. reflexa which is a rapid, , and eco-safe approach. This could be a safe and useful technology for mosquito control.